Use of alternative products to control Ceratocystis frimbriata in kiwi seedlings - Pansera, Marcia Regina; Vergani, Cintia Thais; Santos, Murilo César dos (Revista Interdisciplinar de Ciência Aplicada, 2023)
In the state of Rio Grande do Sul (Brazil) is the largest producer of kiwi, but its productivity has been threatened due to the Ceratocystis fimbriata pathogen. This paper aimed to evaluate the efficiency of essential oils of fennel and Cymbopogon citratus (lemongrass), Pipper nigrum (pepper) and pyrolenous extracts, and Aliette (Fosetyl-Al) fungicide in the control of C. fimbriata on kiwi in vitro and in vivo tests. The treatments for the in vitro test were the following: essential oil of Foeniculum vulgare (fennel) and lemongrass at the concentrations of zero, 0,01 %, 0,05 %, 0,10 %, 0.15 %, and 0.20 % v/v. For pepper extract, the concentrations used were zero, 0,05 %, 0,10 %, 0.25 %, and 0.50 % v/v. For pyroligneous extract, the concentrations used were the following ones: 0,05 %, 0,10 %, 0,25 %, and 0.50 % v/v and fosetyl-Al fungicide (250 g/100 L). The outline was completely randomized with five repetitions, each plot consisting of a Petri dish. For the in vivo assay, seedlings of the cultivar Bruno of one-year-old were used, and they were cultivated in five-liter land pots and kept in a greenhouse. The inoculation occurred through sterilized paper discs, with a diameter of 0.5 cm, immersed in a suspension of the pathogen on a previously provoked injury. The treatments were done through the essential oil of fennel and lemongrass at a dose of 0.20 % and fosetyl-Al (250 g/100 L). The results were submitted to the analysis of variance and the means were compared by the Scott-Knott test with 5 % error probability. It was concluded that the essential oils of lemongrass and fennel, at the concentrations of 0.10, 0.15 and 0.20 % v/v, inhibited completely (100 %) the growth of C. fimbriata. The pepper extract had no effect on the growth of the pathogen at the concentration of 20 % v/v. And for the in vivo assay, no treatment showed satisfactory disease control. however, future studies with higher doses may be carried out.